2018
DOI: 10.18632/oncotarget.26100
|View full text |Cite
|
Sign up to set email alerts
|

Can computer-aided diagnosis assist in the identification of prostate cancer on prostate MRI? a multi-center, multi-reader investigation

Abstract: For prostate cancer detection on prostate multiparametric MRI (mpMRI), the Prostate Imaging-Reporting and Data System version 2 (PI-RADSv2) and computer-aided diagnosis (CAD) systems aim to widely improve standardization across radiologists and centers. Our goal was to evaluate CAD assistance in prostate cancer detection compared with conventional mpMRI interpretation in a diverse dataset acquired from five institutions tested by nine readers of varying experience levels, in total representing 14 globally spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 39 publications
2
78
0
Order By: Relevance
“…The use of more quantitative or automated methods for PCa detection from MRI is therefore clinically desirable. The addition of quantitative metrics to subjective PI‐RADS improves accuracy with improved interobserver agreement . Comprehensive reviews of computer‐aided systems (CAD) developed for PCa detection using prostate MRI are available .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of more quantitative or automated methods for PCa detection from MRI is therefore clinically desirable. The addition of quantitative metrics to subjective PI‐RADS improves accuracy with improved interobserver agreement . Comprehensive reviews of computer‐aided systems (CAD) developed for PCa detection using prostate MRI are available .…”
mentioning
confidence: 99%
“…The addition of quantitative metrics to subjective PI-RADS improves accuracy 8 with improved interobserver agreement. 9 Comprehensive reviews of computer-aided systems (CAD) developed for PCa detection using prostate MRI are available. 10,11 Generally, developed CAD methods for PCa detection require prostate zonal segmentation, feature representation within the region of interest (PZ or transition zone [TZ]), and PCa localization.…”
mentioning
confidence: 99%
“…Standardising the interpretation of prostate MRI with the PI-RADS did not solve the problem of suboptimal inter-reader agreement [19], nor eliminate cancer missing (miss rate up to 30% in some series) [48]. This might partly depend on limitations inherent to the PI-RADS lexicon and interpretation rules [1].…”
Section: Less Variability From Human Readersmentioning
confidence: 99%
“…In most studies, this tool has been evaluated as a radiologist's assistant, with the human reader assuming the final decision on the nature of the findings prompted by CAD. There are plenty of promising results in literature in this regard, as exemplified by a recent multicentre and multireader study in which CAD-assisted readings across different vendors and institutions showed a sensitivity for index-lesions comparable to that of non-assisted readings using PI-RADS version 2 [48]. CAD also helped less experienced readers to diagnose more TZ cancers, and reduced reading time.…”
Section: Less Variability From Human Readersmentioning
confidence: 99%
See 1 more Smart Citation